ChemInform Abstract: Iron‐Catalyzed Four‐Member Multicomponent Reaction for Assembly of (E)‐6‐Arylvinyl‐3, 4‐dihydropyrimidin‐2(1H)‐ones. Issue 3 (29th December 2015) - Zhang, Zhiguo; Zhang, Lianqiang; Duan, Xinyu; Yan, Xiangqian; Yan, Yan; Liu, Qingfeng; Liu, Tongxin; Zhang, Guisheng
Abstract: Starting from β‐ketoamides, urea, and various aryl aldehydes a scalable high‐yielding one‐step access to the title products is developed.